2016
DOI: 10.1177/0022034516646098
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Early Dental Implant Failures

Abstract: Abstract:The purpose of the present study was to assess the influence of local and systemic factors on the occurrence of dental implant failures up to the 2nd stage surgery (abutment connection). This retrospective study is based on 2,670 patients who received 10,096 implants and were consecutively treated with implant-supported prostheses between 1980 and 2014 at one specialist clinic. Several anatomical-, patient-, health-, and implant-related factors were collected. Descriptive statistics were used to descr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
226
6
10

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 226 publications
(262 citation statements)
references
References 41 publications
20
226
6
10
Order By: Relevance
“…In addition, low bone density at implant locations has been previously described to be influential on implant failure. 5,24 Using GEE analyses, Chrcanovic et al 25 have likewise found most implant failures in type IV bone.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, low bone density at implant locations has been previously described to be influential on implant failure. 5,24 Using GEE analyses, Chrcanovic et al 25 have likewise found most implant failures in type IV bone.…”
Section: Discussionmentioning
confidence: 98%
“…The term early implant failure used in this report refers to failure in the first year, chosen for QI purposes. Other reports of early implant failure have had different study purposes and therefore used various time intervals to define the event of interest, such as “less than or equal to 1 year of implant prosthesis loading,” “up to second stage surgery,” and “up to abutment connection.” Papers summarizing multiple reports also have recognized this variability. One review that included seven primary studies conceptually described the time period as representing a “failure to establish osseointegration,” whereas a systematic review of nine primary studies described the data as being representative of failure “before abutment connection.”…”
Section: Discussionmentioning
confidence: 99%
“…Only implant arch location has significant association with implant failure based on log-rank test analysis. Although some studies reported contradictory results that implant survival rate has no correlation with the anatomic location of the implant, 17,26,27 there are various studies that reported favorable results in mandibular implants than that of the maxillary implants. 16,[28][29][30] A recent meta-analysis that includes 54 clinical studies of no less than 3 year follow up period were evaluated, and resulted to an annual implant failure rate that is significantly higher in that of the maxilla than the mandible.…”
Section: -14mentioning
confidence: 99%
“…[12][13][14] Despite of numerous papers reporting high implant survival and success rates, implant failures influenced by local and systemic risk factors are still inevitable and showed contradictory results. [15][16][17] In addition, assessment of Korean ethnic characteristics such as arch form, dietary patterns, bone quality, clench force and other risk fac-…”
Section: Introductionmentioning
confidence: 99%